Features mathematical description of the stabilization system and determine the course of movable object - Сущенко, О.А.; Луцко, Д.О.; Єрмакова, Є.О. (Proceedings of National Aviation University (archive), 2008)
Features of the mathematical description of the system for moving object stabilization and course determinatio. The basic features of the mathematical formulation of the system for moving object stabilization and course determination are analysed. Approaches to taking into account of the angular rate of base, on which navigation sensors are mounted, large number of operation modes of the system to be studied and presence of the electronic and computing devices in the modern systems are suggested.